Identifikasi Kerusakan Dinding Penahan Tanah Sungai Siak (Studi Kasus Kecamatan Tualang Kabupaten Siak) - Fitridawati Soehardi; Marta Dinata (Jurnal Teknik Sipil Unaya, 2018)
This study aims to identify the problem of damage to retaining walls on the banks of the Siak River, Tualang District, Siak District. The implementation of this research uses the method of direct observation in the field and the method of direct interviews with the community around the research location. The results of the data obtained are presented in the form of images of damage to the retaining wall. Conditions of Siak River Displacement, Tualang District, Siak Regency Shows a high level of damage both on the banks of natural rivers and those that have been given cliff protection. Some locations experience abrasion and erosion processes, especially in areas that are still natural. Damage to Siak Riverbanks is caused by natural factors and anthropogenic factors. Natural factors can be strong currents and waves caused by community transportation activities and factories around the Siak River environment. So that it can result in abrasion, damage to ecosystems, and damage to cliff safety buildings. While the Anthropogenic Factor is the behaviour of the community and the factory around Sungai Siak which does not comply with regional regulations and the applicable rules.